2007
DOI: 10.1177/1087057106295895
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescence Resonance Energy Transfer as a Screening Assay: Focus on Partial and Inverse Agonism

Abstract: The reported data for compound screening with the bioluminescence resonance energy transfer (BRET 2 ) assay is very limited, and several questions remain unaddressed, such as the behavior of agonists. Eleven β2 adrenergic receptor (β2-AR) agonists were tested for full or partial agonism in an improved version of the receptor/β-arrestin2 BRET 2 assay and in 2 cyclic adenosine monophosphate (cAMP) assays (column cAMP assay and ALPHAscreen™ cAMP assay). Tested in the highly sensitive ALPHAscreen™ cAMP assay, all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 25 publications
4
19
0
Order By: Relevance
“…Hypertension, angina, IHD, heart failure (Helfand et al, 2007;Baker et al, 2011) Bucindolol 8.92 (Ponicke et al, 2002Baker, 2010) ↑ 9.40 (Baker, 2010) Nonselective bAR antagonist Heart failure (Pauwels et al, 1991) .5.00 (Galandrin and Bouvier, 2006) Carvedilol 9.02-9.40 (Ponicke et al, 2002;Hoffmann et al, 2004;Baker, 2005) ↑ 9.10 (Baker et al, 2003) a 1 AR and bAR antagonist Hypertension, IHD, heart failure, post-MI (Helfand et al, 2007;Ram, 2010;Baker et al, 2011) .5.00 (Galandrin and Bouvier, 2006) (2)-Epinephrine 5.99-6.54 (Frielle et al, 1988;Del Carmine et al, 2002;Hoffmann et al, 2004;Baker, 2010) ↑ 7.74-8.22 (Liapakis et al, 2004;Elster et al, 2007;Baker, 2010) Nonselective endogenous aAR and bAR agonist Allergic reactions, asthma, cardiac failure, hemorrhage, shock (McLeanTooke et al, 2003)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension, angina, IHD, heart failure (Helfand et al, 2007;Baker et al, 2011) Bucindolol 8.92 (Ponicke et al, 2002Baker, 2010) ↑ 9.40 (Baker, 2010) Nonselective bAR antagonist Heart failure (Pauwels et al, 1991) .5.00 (Galandrin and Bouvier, 2006) Carvedilol 9.02-9.40 (Ponicke et al, 2002;Hoffmann et al, 2004;Baker, 2005) ↑ 9.10 (Baker et al, 2003) a 1 AR and bAR antagonist Hypertension, IHD, heart failure, post-MI (Helfand et al, 2007;Ram, 2010;Baker et al, 2011) .5.00 (Galandrin and Bouvier, 2006) (2)-Epinephrine 5.99-6.54 (Frielle et al, 1988;Del Carmine et al, 2002;Hoffmann et al, 2004;Baker, 2010) ↑ 7.74-8.22 (Liapakis et al, 2004;Elster et al, 2007;Baker, 2010) Nonselective endogenous aAR and bAR agonist Allergic reactions, asthma, cardiac failure, hemorrhage, shock (McLeanTooke et al, 2003)…”
Section: Resultsmentioning
confidence: 99%
“…Hypertension, heart failure (Ram, 2010;Baker et al, 2011) (2)-Norepinephrine 4.19-5.41 (Frielle et al, 1988;Hoffmann et al, 2004;Del Carmine et al, 2002;Baker, 2010) ↑5.61-7.46 (Liapakis et al, 2004;Elster et al, 2007;Baker, 2010) Nonselective endogenous aAR and bAR agonist Severe hypotension (Ferguson-Myrthil, 2012) Pindolol 8.32-9.32 (Pauwels et al, 1988;Del Carmine et al, 2002;Hoffmann et al, 2004;Baker, 2010) ↑ 8.96 (Baker et al, 2003) Nonselective bAR antagonist Hypertension (Helfand et al, 2007) ↓ 7.44 (Chidiac et al, 1994) (6)-Propranolol 9.08-9.37 (Del Carmine et al, 2002;Ponicke et al, 2002;Hoffmann et al, 2004;Baker, 2005) ↓ 8.10-9.17 (Baker et al, 2003;Galandrin and Bouvier, 2006) Noncardioselective bAR antagonist Hypertension, angina, atrial arrhythmia, portal hypertension, anxiety, tremor, thyrotoxicosis, migraine …”
Section: Resultsmentioning
confidence: 99%
“…BRET-The protocol for BRET measurements was developed for the Mithras LB 940 plate reader (Berthold Technologies) as described previously (15,16). Briefly, 48 h after transfection, the cells were harvested and washed twice in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…For the bioluminescence resonance energy transfer (BRET) assay, the B2AR was tagged C-terminally with Renilla luciferase and cloned into the pcDNA3.1ϩ vector. ␤-arrestin2 was cloned into pcDNA3.1ϩ vector and tagged N-terminally with green fluorescent protein (GFP) as described previously (15,16).…”
Section: Methodsmentioning
confidence: 99%
“…One, close to the inactive, s ~0.2, was marginally (~1 kcal/mol) more stable than the second state, at s ~0.6. This type of free energy profile illustrates possible reasons for some studies having found alprenolol to behave in different ways in different assays: most notably, as an inverse agonist (Elster et al 2007; Hopkinson et al 2000) or as a partial agonist (Callaerts-Vegh et al 2004). …”
Section: 3 Activation Mechanisms In Gpcrsmentioning
confidence: 81%